Cloning and in silico analyses of mads-box genes isolated from calyx tissues of Hibiscus sabdariffa L. var. umkl - Othman, Siti Norhidayah (2015)
Flower organ development is mainly controlled by genetic factor. MADS-box transcription factor genes play a crucial role in controlling the development of calyx in flowering plants. Hibiscus sabdariffa L. var. UMKL (roselle) is cultivated in Malaysia mainly for its calyx which is high with vitamin C and anthocyanin content. Unfortunately, the genetic information regarding the flowering pathway of roselle is very scarce. It is critical to understand the genetics underlying roselle‟s flower developmental process by studying on genes related to its agronomic trait for the development of genetic markers and improvement of planting material. Hence, two MADS-box genes, designated as HsMADS1 and HsMADS2 were isolated from the young and mature calyx tissues of H. sabdariffa using 3‟- RACE PCR and primer walking approaches. Both HsMADS1 and HsMADS2 CDS were consisted of 951 bp and 981 bp nucleotides, and encoded for putative proteins of 244 amino acids, respectively. The assembled nucleotides sequence of HsMADS1 and HsMADS2 genes obtained were 3,050 bp and 2,791 bp nucleotides, respectively. HsMADS1 was predicted to have 7 exons, 6 introns and HsMADS2 was consisted of 8 exons, 7 introns. Interproscan analysis showed that the deduced amino acids sequences of HsMADS1 and HsMADS2 possessed the MADS and K-box domains. The prediction of the distinct K-domain provided a strong indication that HsMADS1 and HsMADS2 belong to the type II (MIKC-type) of MADS-box gene. Specific motifs predicted at the C-terminal of their protein sequences suggested that HsMADS1 and HsMADS2 might belong to two different subfamilies of SEPALLATA and AGAMOUS-like 6, respectively under the same Class E of MADS-box superfamily. The function of the genes based on the phylogenetic analysis suggested that HsMADS1 possibly involved in the expression of SEP gene in stem, leaf, bud and flower organs of roselle, whereas HsMADS2 may probably involve in the late expression of floral tissue for stem branching. Template identification results showed that HsMADS1 and HsMADS2 were respectively 43% and 38% accurate to Crystal structure of MADS-box/Myocyte Enhancer Factor-2 from Homo sapiens (PDB:1N6J). The homology modeling of HsMADS1 and HsMADS2 demonstrated that both genes shared the same topology of β-α-β-α-α-α and suggesting that the molecular functions of both proteins may be involved in DNA binding and also act as transcriptional repressor or activator in a calcium-dependent manner. The differences in the nucleotide sequences, protein sequences, primary structures, secondary structures and 3D protein structures of HsMADS1 and HsMADS2 allows the assumption that both genes might be different genes involved in the development of young and mature calyx tissues of roselle. Nevertheless, further characterizations need to be carried out in order to confirm the functions of both genes.